Quality of Life of Patients with Diabetes Mellitus - Harith Ahmed Mohammed Mohammed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The aim of the study is to assess he quality of life of diabetics. Method: This is a descriptive cross-sectional study. 200 adults with diabetes, including 110 females and 90 males, were randomly selected from patients receiving treatment in Sharqat General Hospital in Salah al-Din Governorate.Data collection took place between January 1th, 2022 and February 5th, 2022 through the use of an interview. The data was analyzed by applying descriptive statistical analysis that included number, percentage, mean, standard deviation, p-value and anova. Results: When it comes to age groups, the participants were mostly from the age group of 57 years and older (40,5%). The results showed that diabetes was more prevalent in females than in males (55%). The sample comprised almost all married patients (97,5%). As for the education level, a great majority of the participants were primary school graduates (43,5%). Conclusions: This study supported the effect of diabetes on the quality of life of patients in our country. It was also observed that the information obtained about the disease was acceptable, but the safety precautions against the disease were weak. Keywords: Diabetes mellitus, Patients, Quality of life.